BLACK AND GOLD IDENTITY. „TATCZËZNA” AND „ÒDRODA” AS KASHUBIAN-CENTRIC MAGAZINES - Kalinowski, Daniel (Porównania, 2014)
The year 1989 and the political and social changes in Poland of that time brought great opportunities of developing a language and culture for the Kashubian cultural tradition. A manifestation of this fact was the appearance in 1990 of the magazine „Tatczëzna”. It was issued for only a year as an editorial initiative of young people, the students of Tri-City universities who had decided to promote the Kashubian social subjectivity. On deciding to start the journal they gave priorities to freshness of their views, emotional authenticity and a desire to reach the possibly widest Kashubian environment. Other periodical – „Òdroda” was a monthly magazine written in Kashubian, which existed since the end of 1999 to January 2006. It came into being as a result of discussions on the issue of the Kashubian identity and nationality. It was radical in terms of expressed ideas, propounding political, administrative and educational proposals. They were announced with much greater zeal and a stronger emotional load than in the main Kashubian and Pomeranian journal – „Pomerania”. For example, through the content of „Tatczëzna” and „Òdroda” one can observe a process of Kashubian self-awareness towards ever greater subjectivity emerging from the space previously controlled by ideological and political censorship. The creators of the above analyzed periodicals took the tasks previously undertaken by the leaders of the Kashubian identity movement, but now expressed them forcefully, even with a certain type of radicalism. Through the medium of publications they were seeking the greatest possible social and political support for their ideas, in which they succeeded only partially.